2010
DOI: 10.1007/s11423-010-9157-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of jigsaw and animation techniques on students’ understanding of concepts and subjects in electrochemistry

Abstract: This study investigated the effect of jigsaw cooperative learning and animation versus traditional teaching methods on students' understanding of electrochemistry in a first-year general chemistry course. This study was carried out in three different classes in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 45 publications
8
62
0
3
Order By: Relevance
“…These findings validate the extensive review of 323 studies yielding 1,691 findings conducted by Johnson & Johnson (2002), which reported that students in cooperative situations academically outperformed students in individualistic settings (effect-size = 0.75). Similar findings have also been noted in recent studies (Yamarik, 2007;Kilic, 2008;Doymus, 2008a&b;Adeyemi, 2008;Sahin, 2010;Doymus, Karacop & Simsek, 2010;Bertucci, Conte, Johnson, & Johnson, 2010;Slavin, 2011) which report that students in CL groups have higher adjusted posttest mean scores than those in conventional lecture groups. The findings of the above research studies have led to strong arguments by various authors that CL is an effective teaching pedagogy for schools.…”
Section: Achievementsupporting
confidence: 88%
“…These findings validate the extensive review of 323 studies yielding 1,691 findings conducted by Johnson & Johnson (2002), which reported that students in cooperative situations academically outperformed students in individualistic settings (effect-size = 0.75). Similar findings have also been noted in recent studies (Yamarik, 2007;Kilic, 2008;Doymus, 2008a&b;Adeyemi, 2008;Sahin, 2010;Doymus, Karacop & Simsek, 2010;Bertucci, Conte, Johnson, & Johnson, 2010;Slavin, 2011) which report that students in CL groups have higher adjusted posttest mean scores than those in conventional lecture groups. The findings of the above research studies have led to strong arguments by various authors that CL is an effective teaching pedagogy for schools.…”
Section: Achievementsupporting
confidence: 88%
“…According to Doymus, Karacop & Simsek (2010), there are other models, including Reverse Jigsaw, Subject Jigsaw, etc., but this paper will only introduce Jigsaw, Jigsaw 2, Jigsaw 3 and Jigsaw 4.…”
Section: B Types Of Jigsaw Modelmentioning
confidence: 99%
“…In other words, he modified Jigsaw so that the individual evaluation will influence the group score and eventually the group reward. This means that there is a competition between groups (Doymus, Karacop & Simsek, 2010). Jeong (2006) stated the following to be the difference between Jigsaw 2 and Jigsaw.…”
Section: ) Jigsawmentioning
confidence: 99%
“…The use of multimedia creates the environment where students can visual the abstract chemical processes via animation and video in macroscopic, microscopic and symbolic levels (Bowen, 1998;Burke et al 1998;Rodrigues et al 2001;Russell et al 1997). Studies (Doymus, 2010;Gois & Giordan, 2009;Lerman & Morton, 2009) have been carried out and results showed that animation and simulation using ICT can help students to visualize and hence enhance students' understanding in learning abstract chemistry topics.…”
Section: The Use Of Ict In Teaching and Learningmentioning
confidence: 99%